In-situ catalysis of green lubricants into graphitic carbon by iron single atoms to reduce friction and wear - Wei Song; Chongyang Zeng; Xiaoyang Ma; Janet S. S. Wong; Chuke Ouyang; Shouyi Sun; Weiwei Zhang; Jianbin Luo; Xing Chen; Jinjin Li (Nature Communications)
Abstract Reducing friction and wear in moving mechanical systems is essential for their intended functionality. This is currently accomplished by using a large variety of anti-friction and anti-wear additives, that usually contain sulfur and phosphorous both of which cause harmful emission. Here, we introduce a series of diesters, typically dioctyl malate (DOM), as green and effective anti-friction and anti-wear additives which reduce wear by factors of 5-7 and friction by over 50% compared to base oil when tested under high pressures. Surface studies show that these impressive properties are primarily due to the formation of a 30 nm graphitic tribofilm that protects rubbing surfaces against wear and hence provides low shear stress at nanoscale. This graphitic tribofilm is prone to form from diesters derived from short-chain carboxylic acid due to their lone pair effect, which stabilizes the carbon free radicals. Furthermore, the formation of this tribofilm is catalyzed by nascent iron single atoms, which are in-situ generated due to the mechanochemical effects during sliding contact. Computational simulations provided additional insights into the steps involved in the catalytic decomposition of DOM by iron and the formation of a graphitic carbon tribofilm. Due to its anti-friction and wear properties, DOM holds promise to replace conventional additives, and thus provides a green and more effective alternative for next-generation lubricant formulations.